Electrospun nanofibers from a multihole spinneret with uniform electric field. Issue 5 (14th June 2013) - Zheng, Yuansheng; Liu, Xuekai; Zeng, Yongchun
ABSTRACT This study presents a multihole spinneret with a metal flat electrode to obtain uniform electric field and meet a high production requirement. We demonstrate that the multihole spinneret produces finer fiber diameters and more concentrated fiber mat compared to the conventional multineedle electrospinnig system. This study focuses on the effect of the electric field distribution on the spinning process and the resultant nanofibers. The three‐dimensional electric field simulation results show that the multihole spinneret creates not only a more uniform electric field, but also a stronger electric field except for the area very close to the spinneret. The measurement of the electric field verifies the simulation results. This study shows that fine fibers, as well as concentrated and thick fiber mat can be obtained by this multihole electrospinning system at a high production rate. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 3221–3228, 2013